Tissue Engineering for the Ovine Rotator Cuff: Surgical Anatomy, Approach, Implantation and Histology Technique, along with Review of Literature. Issue 2 (7th February 2020) - Ahmad, Zafar; Al-Wattar, Zaid; Rushton, Neil
Abstract: Aim : Tissue engineering is a contemporary topic, which is widely discussed in shoulder surgery. The preclinical success of tissue engineering has not yet fully translated to clinical studies. In this study, we present our experience in this subject and discuss measurements to analyze the sheep tissue as comparative model. We also present a comprehensive systematic review of the literature in relation to tissue engineering and rotator cuff. Method: We studied the anatomy, histology and surgical approach of 24 infraspinatus tendons specimens in sheep and focused on certain measurements such as: (1) size of the normal tendon; (2) diameter of the normal footprint; and (3) bone hardness of the footprint using a durometer. Blood from six sheep was obtained and processed to produce platelet rich plasma using both the Harvest Smartprep and Cascade kit. We then outlined an approach to the infraspinatus tendon footprint in preparation for implantation of a biological augmentation material, which was repaired using a double row technique. This was followed by a histological analysis. Results: The average measurements of the footprint were 21 mm ×21 mm, the tendon length was 35.1 mm and the width proximal and distal was 21.9 and 14 mm, respectively. The average bone hardness at the 12, 3, 6, and 9 o'clock position was 64.1, 52.3, 50.1, and 37.7 respectively. Central footprint and lateral edge hardness was 44.8 and 43.4. Only the Harvest Smartprep and using a modified method, was able to produce a platelet concentration factor of 4. The Cascade method was unable to concentrate sheep blood. Conclusion: The sheep model is a suitable tissue for studying the rotator cuff. The researcher must be aware of certain interspecies caveats. Clinical tissue engineering and surgical techniques must be modified in order to be suitable when using sheep model.